Refinement of methods of monitoring of psychophysiological states of air operators as a route of a heightening of safety of flights - Ударцева, Т. Є. (Proceedings of National Aviation University (archive), 2021)
The deficiencies of an existing system of learning are considered psychophysiological possibilities and limitations of air operators. The necessity of usage of complex methods of psychophysiological selection, definition of work capacity and reliability is justified.